The diverging trends of male and female bottom earnings in Germany - Eliana Coschignano; Robin Jessen (Deutsches Institut für Wirtschaftsforschung (DIW), 2025)
Men at the bottom quintile of the German male earnings distribution had lower average earnings in 2019 than in 2001. In contrast, female earnings have increased throughout the distribution. What explains these diverging trends and how did they translate into changes in net income? Data from the Socio-Economic Panel (SOEP) reveal that the drop in bottom male earnings is mostly due to a decrease in work hours, while hours worked of females with low earnings have increased. Changes in socio-demographic characteristics explain little of the evolution of income inequality. Households and the welfare state have cushioned much of low-earning men's income drop, while disposable incomes of women have increased by less than their earnings. Finally, earnings poverty is persistent: About half of individuals in the bottom quintile are still in the bottom quintile after five years.
Keywords: D31; I38; J3; 330; income inequality; earnings inequality; working hours; decomposition